Pengembangan Kawasan Wisata Mangrove Tamo Kelurahan Baurung Kabupaten Majene - Fadli Sahnan; Agus Salim; Jufriadi Jufriadi (Journal of Urban Planning Studies, 2020)
This study aims to determine the direction of the development of Mangrove Tourism Tamo Neighborhood, Baurung Village, Majene Regency. Analytical techniques used is descriptive. Tamo Mangrove Tourism Development Baurung Village, Majene Regency, still needs attention and proper handling of the local government. Tourism development Tamo Mangrove is currently expected to become one of the ecotourism areas in Majene Regency which can be a driver for improvement local economy. Therefore, collaboration with local communities and the government is very needed in the management and maintenance of the area the development of tamo mangrove tourism in order to be more improved and maintained the sustainability of the mangrove itself. From the results of the study it can be concluded that tamo mangrove tourism development in Baurung Village, Majene Regency still lacking in aspects of tourism supporting infrastructure, community participation, waste management, and management of tourism promotion itself